ATLÂNTICO NEGRO PAIOL: COMO ESTÃO SENDO CONDUZIDAS AS QUESTÕES DE RAÇA E ETNIA NAS AULAS DE LÍNGUA INGLESA? - Camargo, Mábia (2012)
The purpose of this study is to understand how issues of race and ethnicity are being treated in the English as a Foreign Language classes. The locus school of the research is a public school located in the district of Entre Rios, which is formed by five Swabian colonies, in the city of Guarapuava-PR. The classroom observed is composed of students who live on the outskirts of the district, students who live in rural communities and farms between the city of Guarapuava and Pinhão, and also students who live in the Invernada Paiol de Telha Community, a quilombola settlement located in the Socorro Colony. The theoretical base used in this research was constructed from studies about: critical literacy, social-identity theory and the issue of race / ethnicity (MCLAREN E LANKSHEAR,1993, MOITA LOPES, 2002, FERREIRA, 2006, KLEIMAN,1995, PENNYCOOK, 1998, STREET, 1995, BAUMAN, 2005, MUNANGA, 2004). As well as official documents, for example, Federal Law 10.639/2003, which demands the teaching of History and Afro-Brazilian Culture in Basic Education, and the DCEs (Parana State Curricular Guidelines for EFL). The research is qualitative with an interventionist kind, the working method is an ethnographic case study, where through observations during the period of approximately two months, it was accompanied the work of an EFL teacher in dealing with issues of race and ethnicity. In order that, a teaching unit was designed and implemented in the classes of EFL. The research shows up the issues of identity are characterized by the territorial and the social class notion, because of a hegemonic German identity, the other ethnics (Brazilians and Quilombolas) are forgotten and not enhanced. The need for ongoing training of English Language teachers so that the ethnic and racial issues can be worked satisfactorily in the classroom is primary, because the collected data indicates that ethnic and racial issues were not being worked in EFL classes at the referred school. This study aims to contribute to an education of EFL that satisfies the cultural and political demands in equality of race and ethnicity, and to continue discussions about teacher educational training, viewing an anti-racist education.